Contradictory Results from Single Loop Electrochemical Potentiokinetic Reactivation Test and Oxalic Acid Test for Intergranular Corrosion in 304L Stainless Steels Attributed to Si Grain-Boundary Segregation - LIEW, YAN HAN (Electrochemical Society Inc., 2020)
10.1149/2.1361912jes